The Moral Principles on which Medical Faculty Students at the ‎University of Jordan Depend to Identify Moral Issues and to‏ ‏What ‎Extend such Principles are Influenced by Gender, Study Level, and ‎Nature of Science Understanding Level - "Mohammad Khair" Al-Salamat; Khawla Hasaneen; Talal Al-Zou'bi (My University, 2008)
This study aimed at examining the moral principles on which ‎Medical Faculty students at the University Of Jordan depend to identify ‎moral issues and to what extend such principles are influenced by gender, ‎study level, and nature of science understanding level. The sample of the ‎study consists of (40) male and female students, (20) of them were first-‎year medicine students, the other (20) fourth year. The tools of the study ‎were represented by the nature of science understanding test, and moral ‎principles test. After applying the two tests and for answering the ‎questions of the study, means, standard deviations, frequencies and ‎percentages were counted. (‏2‏‎) and (MANOVA) were used. The results ‎showed‏ :‏That the humanitarian principles (33.8%), the religious ‎principles (30.4%), the autonomy principles (19.6%), the social ‎principles (9.2%), while the beneficial principles was (7.0%). As the ‎results show there were no statistically significant differences between ‎the results of students’ responses on examining moral principles ‎attributed to students’ gender, study level, or nature of science ‎understanding level. The study recommended: reconsidering the moral ‎issues in teaching students of medicine, because it is very important to ‎improve the positive attitudes towards science, and to develop critical ‎analytical moral thinking. The study also recommended conducting ‎similar studies on other students from other levels and specializations.‎

هدفت هذه الدراسة إلى استقصاء المبادئ الأخلاقية التي يستند إليها طلبة كلية الطب في ‏الجامعة الأردنية، وتأثرها بكل من الجنس والمستوى الدراسي ومستوى فهمهم لطبيعة العلم. بلغ ‏عدد أفراد الدراسة (40) طالباً وطالبة، منهم عشرون طالباً وطالبة من مستوى السنة الأولى ‏وعشرون طالباً وطالبة من مستوى السنة الرابعة من كلية الطب في الجامعة الأردنية، وتكونت ‏أدوات الدراسة من اختبار فهم طبيعة العلم واختبار المبادئ الأخلاقية، وبعد تطبيق الاختبارين ‏وللإجابة عن أسئلة الدراسة حسبت المتوسطات الحسابية والانحرافات المعيارية والتكرارات ‏والسب المئوية واستخدم اختبار (‏X‏2) وتحليل التباين المتعدد لتحليل النتائج. وأظهرت النتائج ‏شيوع المبدأ الإنساني بين طلبة كلية الطب بنسبة (33.8%) يلي ذلك المبدأ الديني بنسبة ‏‏(30.4%) ثم المبدأ الاستقلالي بنسبة (19.6%) وجاء المبدأ المجتمعي بنسبة (9.2%) واحتل ‏المبدأ النفعي المرتبة الخامسة بنسبة (7.0%). كما أظهرت النتائج عدم وجود فرق ذي دلالة ‏إحصائية بين نتائج استجابات الطلبة على اختبار المبادئ الأخلاقية يُعزى لمتغيرات الجنس ‏والمستوى الدراسي ومستوى فهم الطلبة لطبيعة العلم. في ضوء النتائج أوصت الدراسة بالاهتمام ‏بالقضايا الأخلاقية في تدريس طلبة كلية الطب لما لها من أهمية في تنمية الاتجاهات الإيجابية ‏نحو العلم وتطوير التفكير الأخلاقي التحليلي الناقد لديهم. وإجراء دراسات على طلبة من ‏مستويات أخرى وتخصصات جديدة.‏
المبادئ الأخلاقية التي يستند إليها طلبة كلية الطب في الجامعة الأردنية في إصدار حكمهم على ‏القضايا الأخلاقية، ومدى تأثرها بكل من الجنس والمستوى الدراسي ومستوى فهمهم لطبيعة ‏العلم